The method of organizing the pedagogical process of application of Information Technology in the Independent Education of students in the science of Information Technology in medicine using information technologies - Asadova Yulduz.Ismatovna (Zien Journals, 2022)
Choosing a complex set of tools, commonly referred to as Learning Management Systems (LMS), to create the perfect combination of traditional classroom classes and the most appropriate components of an e-learning course has become common practice. Our institutions have chosen an open source LMS Moodle. After many years of its application in everyday pedagogical practice, we were inspired to analyze the effect of this platform. This article presents the results of surveys conducted to familiarize students and teachers with experiments with Moodle.
Keywords: learning management system; privacy; security; experience